An R2R3‐MYB transcription factor represses the transformation of α‐ and β‐branch carotenoids by negatively regulating expression of CrBCH2 and CrNCED5 in flavedo of Citrus reticulate. Issue 1 (6th July 2017) - Zhu, Feng; Luo, Tao; Liu, Chaoyang; Wang, Yang; Yang, Hongbin; Yang, Wei; Zheng, Li; Xiao, Xue; Zhang, Mingfei; Xu, Rangwei; Xu, Jianguo; Zeng, Yunliu; et al.
Summary: Although the functions of carotenogenic genes are well documented, little is known about the mechanisms that regulate their expression, especially those genes involved in α ‐ and β‐branch carotenoid metabolism. In this study, an R2R3‐MYB transcriptional factor (CrMYB68) that directly regulates the transformation of α‐ and β‐branch carotenoids was identified using Green Ougan (MT), a stay‐green mutant of Citrus reticulata cv Suavissima . A comprehensive analysis of developing and harvested fruits indicated that reduced expression of β‐carotene hydroxylases 2 ( CrBCH2 ) and 9‐cis‐epoxycarotenoid dioxygenase 5 ( CrNCED5 ) was responsible for the delay in the transformation of α‐ and β‐carotene and the biosynthesis of ABA. Additionally, the expression of these genes was negatively correlated with the expression of CrMYB68 in MT. Further, electrophoretic mobility shift assays (EMSAs) and dual luciferase assays indicated that CrMYB68 can directly and negatively regulate CrBCH2 and CrNCED5 . Moreover, transient overexpression experiments using leaves of Nicotiana benthamiana indicated that CrMYB68 can also negatively regulate NbBCH2 and NbNCED5 . To overcome the difficulty of transgenic validation, we quantified the concentrations of carotenoids and ABA, and gene expression in a revertant of MT. The results of these experiments provide more evidence that CrMYB68 is an important regulator of carotenoid metabolism.